2012
DOI: 10.1021/bc300110b
|View full text |Cite
|
Sign up to set email alerts
|

In Situ SVVYGLR Peptide Conjugation into Injectable Gelatin-Poly(ethylene glycol)-Tyramine Hydrogel via Enzyme-Mediated Reaction for Enhancement of Endothelial Cell Activity and Neo-Vascularization

Abstract: Tissue engineering therapies require biocompatible and bioactive biomaterials that are capable of encouraging an angiogenic response for effective tissue regeneration. In this study, a SVVYGLR peptide, which functions as a potent angiogenic factor, was conjugated into injectable gelatin-poly(ethylene glycol)-tyramine (GPT) hydrogels in situ to enhance endothelial cell activities and neo-vascularization. SVVYGLRGGY (SV-Y) conjugated GPT (SV-GPT) hydrogels were formed in situ via enzyme-mediated reaction using h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 34 publications
1
45
0
Order By: Relevance
“…To prepare AXF foams, 600 mg of AXF dry powder alone or along with 65 mg of silver sulfadiazine was added to 10 mL of deionized water, stirred, and shaken until dissolved completely. Next, 50 µL of 1 mg/mL HRP solution and 60 µL of (3% w/v) H 2 O 2 were each added to the AXF solutions and stirred to initiate enzymatic crosslinking . Immediately, the prepared solution was poured into a 100 mm Petri‐dish and placed in an ultrasonic bath (1510R‐DTH Branson) for 30 min sonication at room temperature with a fixed frequency of 42 kHz.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To prepare AXF foams, 600 mg of AXF dry powder alone or along with 65 mg of silver sulfadiazine was added to 10 mL of deionized water, stirred, and shaken until dissolved completely. Next, 50 µL of 1 mg/mL HRP solution and 60 µL of (3% w/v) H 2 O 2 were each added to the AXF solutions and stirred to initiate enzymatic crosslinking . Immediately, the prepared solution was poured into a 100 mm Petri‐dish and placed in an ultrasonic bath (1510R‐DTH Branson) for 30 min sonication at room temperature with a fixed frequency of 42 kHz.…”
Section: Methodsmentioning
confidence: 99%
“…Next, 50 mL of 1 mg/mL HRP solution and 60 mL of (3% w/v) H 2 O 2 were each added to the AXF solutions and stirred to initiate enzymatic crosslinking. 29 Immediately, the prepared solution was poured into a 100 mm Petri-dish and placed in an ultrasonic bath (1510R-DTH Branson) for 30 min sonication at room temperature with a fixed frequency of 42 kHz. After sonication, the solution was allowed to sit at room temperature for 3 h to cure.…”
Section: Scaffold Preparationmentioning
confidence: 99%
“…Some reports suggest that the ECs exhibit higher binding affinity to cyclic RGD (cRGD) than linear RGD, likely because the conformation of cRGD is closer to that of the native ligand. Similarly, other adhesive protein‐derived peptide sequences have also been found to have a significant effect on EC adhesion and migration (displayed in Table ) . ECs are sensitive to the physical and chemical properties of the underlying substrate and to hemodynamic changes.…”
Section: Ecs and In Vitro Endothelializationmentioning
confidence: 98%
“…Park et al prepared gelatin-PEG-Ph hydrogels with the endothelialc ell binding se- quenceS er-Val-Val-Tyr-Gly-Leu-Arg (SVVYGLR) throught he HRP-mediated hydrogelation of as olution containingg elatin-PEG-Ph and SVVYGLRGGY. [30] The incorporation of the peptide induced attachment and proliferation of human umbilical vein endothelial cells (HUVECs) on the hydrogel in vitro and new vascular formation in vivo, compared with that of gelatin-PEG-Ph alone. Wang et al demonstrated enhanced HUVEC activity in an HA-Ph hydrogel both in vitro and in vivo by conjugating an Arg-Gly-Asp (RGD) peptide with as mall PEG linker terminated with two Ph groups.…”
Section: Conjugation Of Polymer-ph and Small Moleculesmentioning
confidence: 99%